Efektivitas Pembelajaran Berbasis AI dan Augmented Reality dalam Meningkatkan Literasi Digital dan Fungsi Eksekutif Otak Siswa SD: Tinjauan Literatur Sistematis - Fadhilah, Mutik; Isma Nuriza, Khusnul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The digital transformation in education demands a new approach to learning, especially at the elementary school level. This study aims to describe the development of students' executive brain functions through AI- and AR-based learning, describe the development of students' executive brain functions through AI- and AR-based learning, and identify supporting and inhibiting factors in the implementation of these technologies. This study uses a systematic literature review method. This research design refers to the PRISMA approach. The results of the study indicate that the integration of AI and AR in learning has been proven to improve students' ability to understand, evaluate, and utilize digital information critically, while stimulating the development of working memory, impulse control, and focused attention, which are part of the brain's executive functions. Supporting factors such as digital infrastructure, teacher competence, and flexible education policies are crucial for the successful implementation of these technologies. This study concludes that AI and AR are not merely visual aids, but can be a key pedagogical approach to shaping 21st-century learners. These findings recommend the need for comprehensive policy support and teacher training to maximize the potential of technology in elementary education.